Chīwit thī mankhong thī Bān Mankhong Mư̄ang Čhanthaburī - Salinthip Chīangthōng (Sathāban Phatthanā ʻOngkō̜n Chumchon, 2010)
Housing development for the urban community in Chanthaburi, Eastern Thailand.